Urban flash floods modeling in Mzuzu City, Malawi based on Sentinel and MODIS data - Gumindoga, Webster; Liwonde, Chikumbutso; Rwasoka, Donald Tendayi; Kowe, Pedzisai; Maviza, Auther; Magidi, James; Chikwiramakomo, Lloyd; Mavaringana, Moises de Jesus Paulo; Tshitende, Eric (Frontiers in Climate, 2024)
Floods are major hazard in Mzuzu City, Malawi. This study applied geospatial and hydrological modelling techniques to map flood incidences and hazard in the city. Multisensor (Sentinel 1, Sentinel 2 and Moderate Resolution Imaging Spectroradiometer (MODIS)) Normalized Difference Vegetation Index (NDVI) datasets were used to determine the spatio-temporal variation of flood inundation. Ground control points collected using a participatory GIS mapping approach were used to validate the identified flood hazard areas. A Binary Logistic Regression (BLR) model was used to determine and predict the spatial variation of flood hazard as a function of selected environmental factors. The Hydrologic Engineering Center's Hydrologic Modeling System (HEC-HMS) was used to quantify the peak flow and runoff contribution needed for flood in the city. The runoff and peak flow from the HEC-HMS model were subjected to extreme value frequency analysis using the Gumbel Distribution approach before input into the Hydrologic Engineering Centre River Analysis System (RAS) (HEC-RAS). The HEC-RAS model was then applied to map flood inundated areas producing flood extents maps for 100, 50, 20 and 10-year return periods, with rain-gauge and Climate Prediction Center MORPHed precipitation (CMORPH) satellite-based rainfall inputs. Results revealed that selected MODIS and Sentinel datasets were effective in delineating the spatial distribution of flood events. Distance from the river network and urban drainage are the most significant factors (p< 0.05) influencing flooding. Consequently, a relatively higher flood hazard probability and/susceptibility was noted in the south-eastern and westernmost regions of the study area. The HEC-HMS model calibration (validation) showed satisfactory performance metrics of 0.7 (0.6) and similarly, the HEC-RAS model significantly performed satisfactorily as well (p<0.05). We conclude that bias corrected satellite rainfall estimates and hydrological modelling tools can be used for flood inundation simulation especially in areas with scarce or poorly designed rain gauges such as Mzuzu City as well as those affected by climate change. These findings have important implications in informing and/ updating designs of flood early warning systems and impacts mitigation plans and strategies in developing cities such as Mzuzu.